Effect of elicitation on polyphenol and carotenoid metabolism in butterhead lettuce (Lactuca sativa var. capitata) - Moreno-Escamilla, Jesus Omar; Alvarez-Parrilla, Emilio; de la Rosa, Laura A.; Martinez Ruiz, Nina Del Rocio; Gonzalez Fernandez, Raquel; Orozco-Lucero, Ernesto; Rodrigo Garcia, Joaquin; Gonzalez-Aguilar, Gustavo A.; Garcia-Fajardo, Jorge A.; Jimenez-Hernandez, Fatima Estefania (2020)
The effect of elicitation in butterhead lettuce on carotenoid and polyphenol metabolism was evaluated. Different concentrations of arachidonic acid (AA), salicylic acid (SA), methyl jasmonate (MJ) (15, 45, and 90 μM) and Harpin protein (HP) (30, 60, and 120 mg/L) were applied on red and green butterhead lettuces. Total phenolic and flavonoid content were incremented by MJ (90 μM) in green and red lettuce. Carotenoids were increased in red lettuce (AA; 45 μM). Green lettuce modifies their phenolic acid profile after elicitation with AA and MJ; meanwhile, red lettuce incremented mainly in hydroxycinnamic acids and flavonols, MJ being the elicitor with the highest effect. There was an impact on secondary metabolite enzyme gene transcript concentration. Phenylalanine ammonia-lyase (PAL) and lycopene beta cyclase (LBC) increased in both varieties after elicitation. A relationship between phytochemical increase and the activation of the metabolic pathways after elicitation in butterhead lettuce was observed.